Study of the influence of surface reinforcement on the bearing capacity of ice - Ipatov, Konstantin Igorevich; Vasilyev, Aleksey Sergeyevich; Zemlyak, Vitaliy Leonidovich (Computational Continuum Mechanics, 2019)
Practical experience shows that the physical and mechanical properties of the ice cover are unreliable and can strongly depend on various external factors (the presence of snow and wind at the time of freezing, the ambient temperature), if it is reinforced by traditional methods. In this connection, the problem of increasing the bearing capacity of ice by alternative methods, e.g. by introducing reinforcing elements into the ice, is an urgent problem today. The aim of this work is to determine the effect of various reinforcing materials on the carrying capacity of the ice cover. First, a comparison was made between the results of experimental and numerical studies obtained for the maximum deflections and the carrying capacity of ice samples strengthened with steel reinforcement according to the proposed scheme. Secondly, numerical investigation of the strength of ice upon reinforcement with various composite materials was performed. Experiments on strengthening ice samples with A400 steel reinforcement were carried out on a setup specially designed for simulating pure bending conditions. The destruction of the ice cover occurs under the action of pure bending when the vehicle is moving along it. In numerical experiments, the samples were reinforced with surface reinforcing frames with different physical and mechanical properties. Numerical calculations of the stress-strain characteristics of the ice cover were performed in terms of the physically nonlinear deformation model using the FE software package. The paper gives a qualitative and quantitative assessment of the effectiveness of the use of various composite materials as reinforcing elements. It is shown that the application of reinforcing materials to strengthen the ice cover significantly increases its bearing capacity.